2020
DOI: 10.1177/1053451220910740
|View full text |Cite
|
Sign up to set email alerts
|

Working With Paraeducators: Tools and Strategies for Planning, Performance Feedback, and Evaluation

Abstract: With continued emphasis on inclusive practices, paraeducators are increasingly relied upon as an integral part of instructional service delivery for students with disabilities. However, research consistently reveals that the effective use of paraeducators depends largely on teacher leadership and supervision. Currently, few teacher preparation programs offer meaningful coursework pertaining to managing paraeducators, leaving teachers unprepared for their supervisory role upon entering the field. Incorporating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Each special educator delivered an initial training session and subsequent follow-up coaching sessions until the paraprofessional met the performance criteria for mastery; the initial training and coaching protocols were followed with 100% implementation fidelity across participants and training sessions. Because BST has been highly effective across a range of contexts (e.g., Kirkpatrick et al, 2019), researchers have encouraged its use among special educators for paraprofessional training purposes (Yates et al, 2020). It should be noted that, in the current study, research team members supplied initial training, a structured coaching checklist, and consultative support to guide special educators’ delivery of the BST training elements.…”
Section: Discussionmentioning
confidence: 99%
“…Each special educator delivered an initial training session and subsequent follow-up coaching sessions until the paraprofessional met the performance criteria for mastery; the initial training and coaching protocols were followed with 100% implementation fidelity across participants and training sessions. Because BST has been highly effective across a range of contexts (e.g., Kirkpatrick et al, 2019), researchers have encouraged its use among special educators for paraprofessional training purposes (Yates et al, 2020). It should be noted that, in the current study, research team members supplied initial training, a structured coaching checklist, and consultative support to guide special educators’ delivery of the BST training elements.…”
Section: Discussionmentioning
confidence: 99%
“…Schools will need to determine how to apply well-established paraeducator training practices within the inclusive context. Given the strong research evidence supporting training approaches that were utilized to support paraeducators in the reviewed studies, we recommend that schools develop paraeducator training protocols that include a description of the skill, modeling the skill, practice opportunities, and performance feedback on paraeducator implementation of the skill, with subsequent progress monitoring and feedback once the paraeducator begins implementation with students (Yates et al, 2020).…”
Section: Implications For Practicementioning
confidence: 99%
“…Several studies have shown that with adequate training, paraprofessionals are able to support student academic learning and behavior (Sobeck et al, 2020;Wills et al, 2019). In most cases, this training and supervision falls on the teachers, who are often unprepared for this additional responsibility (Yates et al, 2020). As a result, paraprofessionals report feeling underprepared to take on their roles in the classroom (Douglas et al, 2016).…”
Section: Benefits Of and Barriers To Collaborationmentioning
confidence: 99%